MARKETING SKILLS AS A FACTOR INFLUENCING ADOPTION OF INNOVATIONS ALONG THE MANGO SUPPLY CHAIN IN MERU COUNTY, KENYA - Imaita, Isaiah Gitonga (European Scientific Journal, ESJ, 2014)
The study adopted descriptive survey design. The population of the study consisted of Mango Growers in Meru County and the mango traders and exporters. Meru County was chosen due to the good climatic condition that has made it suitable for mangoes production. This study adopted a probability sampling method to select the respondents for the study. Out of 13,442 farmers, traders and exporters, 447 farmers, 12 traders and 2 exporters were randomly selected for interview. Secondary data used in the study was collected from the Ministry of Agriculture Offices while primary data was collected from the respondents using a structured questionnaire with both open and close ended questions. Both qualitative and quantitative data were used in the analysis. Quantitative data obtained from the field was analyzed using descriptive and inferential techniques. The descriptive techniques adopted were means and frequencies while the inferential technique used were regression and correlation to establish relationship between variables in the study and inferences made. Frequency tables and charts were used to present the findings. The study found out that majority of the traders/exporters were trained on marketing. They had price knowledge, product knowledge and promotion knowledge and majority adopted innovations unlike the growers who had low marketing skills; this would explain why 39% of the produce goes to waste. On traders/ exporters, a significant chi-square relationship was established with innovation given a chi-square value of 9.620 at p=0.047. The study concludes that marketing skills influence buying and selling; and if value chain members had excellent marketing skills, nothing could be going to waste as they would adopt relevant technologies and add value to the produce and meet the customers’ needs. The study recommends that there is need for intense training on market skills on value chain members and stakeholders, either through NGOs and private sector. There is also need for business incubation programs and need to revise training curriculum to cater for marketing skills.